Decacyclene Triimides: Paving the Road to Universal Non‐Fullerene Acceptors for Organic Photovoltaics. Issue 5 (8th November 2013) - Pho, Toan V.; Toma, Francesca M.; Tremolet de Villers, Bertrand J.; Wang, Sarah; Treat, Neil D.; Eisenmenger, Nancy D.; Su, Gregory M.; Coffin, Robert C.; Douglas, Jessica D.; Fréchet, Jean M. J.; Bazan, Guillermo C.; Wudl, Fred; et al.
<x xml:space="preserve">Abstract</x> A novel n‐type material, an alkylated decacyclene triimide (DTI), is utilized in organic photovoltaic devices as the first non‐fullerene acceptor that performs efficiently with the benchmark donor polymer poly(3‐hexylthiophene) (P3HT) as well as various narrow band gap polymers. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>